Микротвердость поверхности нержавеющей стали, модифицированной ионной имплантацией - Гончаров, В.В. (Проблемы машиностроения, 2013)
Исследованы микротвердость и пластичность образцов на основе нержавеющей стали, обработанных с помощью имплантации ионов азота, хрома, алюминия, титана и молибдена. Показана перспективность применения полученных Досліджено мікротвердість і пластичність зразків на основі нержавіючої сталі, оброблених за допомогою імплантації іонів азоту, хрому, алюмінію, титану і молібдену. Показано перспективність застосування отриманих імплантатів в умовах механічного навантаження. The importance of the problem of applied systems synthesis with active components was established. Based on the analysis of literary sources, the optimal processing technology of the stainless steel carrier was chosen. The objective of this paper was formulated, and the task of investigating the mechanical properties of steel-based systems was set. The techniques of obtaining and studying samples were considered. The prospects of applying the obtained composites as working elements of catalysts, heating and electrical equipment, etc., were shown.